Penerapan Metode Quantum Teaching dalam Meningkatkan Hasil Belajar Matematika dalam Materi Bentuk Pangkat dan Akar pada Siswa SMA Negeri 1 Gondang Bojonegoro - Lelia Suretdawati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to improve the results of learning mathematics using quantum teaching models. This research uses the method of action research. The subjects of the study were students and math teachers of grade X SMA Negeri 1 Gondang Bojonegoro, with class X MIPA 1 as a test class and class X MIPA 2 as a research class. The results showed a significant improvement in teacher performance variables in the learning process from cycle I by 62.5% increased to 79.17% in cycle II. In the student's activity variable increased by 67.5% from cycle I to 75.63% in cycle II. Student learning outcomes have also increased by 71.88% to 87.5% and have achieved indicators of success. Quantum teaching model can improve students' learning outcomes.